2021
DOI: 10.21608/jpp.2021.169634
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variability, Heritability and Genetic Advance of Seed Yield and Its Components for Some Promising Genotypes of Faba Bean التباين الوراثي و التوريث في محصول البذور ومکوناته لبعض التراکيب الوراثية الواعدة من الفول البلدي

Abstract: A field experiment designed in randomized complete block design with three replicates was used to evaluate nine promising faba bean lines in F6 with three cultivars: Giza 716, Giza 843 and Sakha 1 under natural infection of chocolate spot disease at the Agricultural Research Station farm in Etay Al-Baroud during 2018/2019 and 2019/2020. Mean squares due genotypes were highly significant for all studied traits in both seasons as a clear evidence for the wide diversity between these genotypes in their pedigree a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Otherwise, Giza-843, Misr-3, Sakha-1, Sakha-3, and Wadi-1 had lower levels of resistance and were susceptible to chocolate spot infection. Similarly, Bouhassan et al 11 ; Beyene et al 13 ; Tekalign, et al 39 ; Waly, et al 40 , and Heiba, et al 41 depicted highly significant variations in chocolate spot resistance evaluated in faba bean genotypes. Sowing date considerably affects available climate variables that significantly impact chocolate spot resistance.…”
Section: Discussionmentioning
confidence: 94%
“…Otherwise, Giza-843, Misr-3, Sakha-1, Sakha-3, and Wadi-1 had lower levels of resistance and were susceptible to chocolate spot infection. Similarly, Bouhassan et al 11 ; Beyene et al 13 ; Tekalign, et al 39 ; Waly, et al 40 , and Heiba, et al 41 depicted highly significant variations in chocolate spot resistance evaluated in faba bean genotypes. Sowing date considerably affects available climate variables that significantly impact chocolate spot resistance.…”
Section: Discussionmentioning
confidence: 94%
“…On the other hand, the remaining traits were high. Previous studies have also reported varying heritability values for different traits, including [26][27][28][29].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported the economic effects of heterosis on yield components, with hybrids having higher heterosis values than the parent for yield components and maturity stage in faba beans [25]. Additionally, Tekalign et al and Waly et al [38,39] reported significant heterosis in F1, which increased by 40% compared to the parents. Furthermore, the yield quantity and quality of F1 were higher than the mean values of better and mid parents [40].…”
Section: Heterosis Potency Ratio and Inbreeding Depressionmentioning
confidence: 92%